Earthquake-Induced pallet sliding in industrial racking systems. (September 2018) - Castiglioni, Carlo A.; Drei, Alberto; Kanyilmaz, Alper; Mouzakis, Harris P.
Abstract: This paper discusses the sliding behaviour of pallets in industrial racking systems under dynamic actions. For this purpose, a summary of the results of an extensive series of dynamic shake-table tests are presented; complete results of this extensive testing campaign may be found in a recently published book. Dynamic and seismic tests have been performed using three beam types with different surface finish materials, in both the Cross-Aisle (CA) and Down-Aisle (DA) directions. Lower and upper bound accelerations were determined from the uniaxial dynamic tests. Several phenomena related to deformations of the supporting beams (i.e. in- and out-of-plane bending) were found to affect the pallet behaviour, in both the CA and DA directions, with sliding occurring at very low acceleration levels. The same behaviour was observed during uniaxial earthquake tests. For biaxial seismic testing, lower bound acceleration in the CA direction was higher than in dynamic cyclic tests, whereas the opposite was observed in the DA direction. Highlights: The paper investigated the sliding behaviour of pallets in industrial racking systems under dynamic actions. A summary of the results of an extensive series of dynamic table tests are presented. Dynamic and seismic tests have been performed using three beam types with different surface finish materials, in both the Cross-Aisle (CA) and Down-Aisle (DA) directions. Lower and upper bound accelerations were determined from the uniaxial dynamic tests.